2010
DOI: 10.1039/c0cc02694h
|View full text |Cite
|
Sign up to set email alerts
|

An unprecedented stereoselective [2+2] cycloreversion of cyclobutanones

Abstract: A one-pot metathetic ring opening of substituted bicyclo[3.2.0]heptenones to linear polyene ketones is described. The reaction proceeds with conservation of the endocyclic (Z)-double bond. Exo-substituted vinylcyclobutanones result in (4Z,6E)-configured trienones, while endo-substituted phenyl derivatives generate (4Z,6Z)-configured dienones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Goeke et al reported a related [2 + 2] cycloreversion process occurring in alkylation reactions of fused cyclobutanones with organolithium reagents. 47 The possible assistance of the ketone group to facilitate the Csp 3 –Csp 3 bond cleavage event would be analogous to that one formerly described in Pd-catalyzed retro-aldol reactions; 20 nevertheless, in those cases a six-membered O , O -palladacycle intermediate is formed, instead of a C , O -palladacycle as might happen in our case.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Goeke et al reported a related [2 + 2] cycloreversion process occurring in alkylation reactions of fused cyclobutanones with organolithium reagents. 47 The possible assistance of the ketone group to facilitate the Csp 3 –Csp 3 bond cleavage event would be analogous to that one formerly described in Pd-catalyzed retro-aldol reactions; 20 nevertheless, in those cases a six-membered O , O -palladacycle intermediate is formed, instead of a C , O -palladacycle as might happen in our case.…”
Section: Resultssupporting
confidence: 79%
“…In this case, either a β-C elimination or a plausible retrocyclization mechanism assisted by the ketone group could operate to render α-methylstyrene 3a along with a Pd­(II) enolate, which would finally undergo a protodepalladation step to afford acetophenone 2a and restore the catalytic Pd­(II) species. Goeke et al reported a related [2 + 2] cycloreversion process occurring in alkylation reactions of fused cyclobutanones with organolithium reagents . The possible assistance of the ketone group to facilitate the Csp 3 –Csp 3 bond cleavage event would be analogous to that one formerly described in Pd-catalyzed retro-aldol reactions; nevertheless, in those cases a six-membered O , O -palladacycle intermediate is formed, instead of a C , O -palladacycle as might happen in our case.…”
Section: Resultssupporting
confidence: 69%
“…We recently reported a novel metathetic cycloreversion of 7-vinyl and aryl bicyclo[3.2.0]hept-2-en-6-ones giving rise to linear polyene ketones. The reaction was triggered by an in situ alkylation with alkyl or aryllithium reagents in the presence of catalytic amounts of Li-chelating agents (e.g., Scheme 1 ) [ 24 ]. The configuration of the newly formed double bond in position 6 was diastereoselectively determined by the configuration of the bicyclic precursor.…”
Section: Introductionmentioning
confidence: 99%
“…1,2-Addition of alkyl lithium reagents with 2a afforded cyclobutenols 4a and 4b . Subsequent ring-opening of 4 in the presence of LDA afforded β,γ-unsaturated enones 5a and 5b in 83% and 89% yields, respectively (Scheme ) …”
mentioning
confidence: 99%